1988
DOI: 10.1007/bf03259935
|View full text |Cite
|
Sign up to set email alerts
|

Valproate-Associated Hepatotoxicity and its Biochemical Mechanisms

Abstract: Intake of the anticonvulsant drug valproic acid, or its sodium salt, has been associated with occasional instances of severe and sometimes fatal hepatotoxicity. Probably at least 80 cases have occurred worldwide. The syndrome affects perhaps 1 in 10,000 persons taking the drug, and usually develops in the early weeks or months of therapy. Most instances have involved children, usually those receiving more than 1 anticonvulsant. Multiple cases have occurred in 2 families. The typical presentation is of worsenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 91 publications
1
54
0
Order By: Relevance
“…First, valproate administration was rapidly fatal in rats at a dose of 1424 mg/kg/day that was expected to yield significantly lower serum concentrations than observed based upon the prior experiments (Figure 2). A literature search failed to locate a known, pathologic basis of acute valproate toxicity in rats; a rare incidence of fulminant heptatoxicity in humans has been reported (Eadie et al 1988). A second challenge is that the relationship between dose and serum concentration is nonlinear; an abrupt increase in serum concentration was observed between the highest two doses in the pilot study (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…First, valproate administration was rapidly fatal in rats at a dose of 1424 mg/kg/day that was expected to yield significantly lower serum concentrations than observed based upon the prior experiments (Figure 2). A literature search failed to locate a known, pathologic basis of acute valproate toxicity in rats; a rare incidence of fulminant heptatoxicity in humans has been reported (Eadie et al 1988). A second challenge is that the relationship between dose and serum concentration is nonlinear; an abrupt increase in serum concentration was observed between the highest two doses in the pilot study (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence has emerged to link the hepatotoxicity of VPA to its metabolism and has been reviewed over the years (Eadie et al, 1988;Abbott and Anari, 1999;Radatz and Nau, 1999). Moreover, a review of mass-balance studies indicated that the total recovery of a VPA dose cannot be completely accounted for in humans (Baillie and Sheffels, 1995), suggesting the existence of yet unknown metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns over its teratogenicity and hepatotoxicity side effect have encouraged the need to develop analogs of VPA devoid of the adverse effects. However, this task is complicated by the fact that the mechanism of action of the drug itself remains to be understood.A large body of evidence has emerged to link the hepatotoxicity of VPA to its metabolism and has been reviewed over the years (Eadie et al, 1988;Abbott and Anari, 1999;Radatz and Nau, 1999). Moreover, a review of mass-balance studies indicated that the total recovery of a VPA dose cannot be completely accounted for in humans (Baillie and Sheffels, 1995), suggesting the existence of yet unknown metabolites.…”
mentioning
confidence: 99%
“…All the rats were raised for 8 consecutive weeks. The duration of the experiment was based on two major factors: 1) VPA-induced microvesicular steatosis was developed in the early weeks of therapy, and 2) the rats treated with an HFD for 8 weeks showed initial evidence of NAFLD [5,27] . Two dose levels of VPA, a therapeutic level (100 mg/kg) and a subtoxic level (500 mg/kg), were selected [28,29] .…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…VPA has broad applications. For this reason, the side effects associated with VPA, especially hepatotoxicity, have aroused widespread global concern [5,6] . Abdominal ultrasound studies showed the presence of non-alcoholic fatty liver disease (NAFLD) in 61% of VPA-treated patients [7] , which suggested a high frequency of changes in asymptomatic hepatic steatosis induced by VPA.…”
Section: Introductionmentioning
confidence: 99%